PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 007 SERUSA MATI - Nurhayati '; Damanhuri Daud Damanhuri Daud; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :This research is motivated by the lack of science learning outcomes of students, with an average grade of 53.75. While the completeness criteria Minimum value (KKM) IPA was 60 Among students, amounting to 24 people only 10 students who achieve KKM with classical completeness 41.67%. This research is Classroom Action Research (CAR) conducted aiming to improve science learning outcomes Elementary School fourth grade students Serusa 007 Dead by implementing STAD cooperative learning model. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results obtained by studying the average learning outcome measures 53.75 before rising 19.77% to 64.38 in cycle I. In the second cycle increased by 47.29% to an average of 79.17. Activities of teachers in the first cycle the first meeting of the percentage of 60% obtained with enough categories, the second meeting had to be 70%. Furthermore, the first meeting of the second cycle activity scores of teachers 75% increase with both categories, at the second meeting increased to 90% with very good category. The results of the data analysis of student activity in the first cycle to 55% with less category, 65% in the second meeting of the students already understand this cycle of learning activities with the implementation of STAD cooperative. And the second cycle students 75% activity score increased with both categories. At the second meeting increased to 85% with very good category. The results of the study in fourth grade Serusa 007 Mati State to prove that the implementation of STAD cooperative learning model to improve learning outcomes Math 007 fourth grade students of SDN Serusa Mati. Keywords: Cooperative Type STAD, Science leaning outcome